2005
DOI: 10.1038/modpathol.3800297
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphoma with distinctive patterns of splenic and bone marrow involvement: clinicopathologic features of two cases

Abstract: Two unusual cases of large B-cell lymphoma with predominant splenic and bone marrow (BM) involvement and similar clinical and histopathologic features are described. Both patients presented with nonspecific constitutional symptoms, unexplained cytopenias, and splenomegaly. Splenectomy revealed diffuse red pulp involvement by large B-cell lymphoma. The perisplenic lymph nodes were also involved diffusely with effacement of normal nodal architecture, excluding a diagnosis of intravascular large B-cell lymphoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Moreover, we observed lymphoma cell surface expression of the CD5 antigen in eight of the ten patients (80%) [8,10,12], including four of our original six patients. Low intensity of the lymphoma cell CD5 antigen might not be detectable by immunohistochemistry (Tables 3 and 6).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Moreover, we observed lymphoma cell surface expression of the CD5 antigen in eight of the ten patients (80%) [8,10,12], including four of our original six patients. Low intensity of the lymphoma cell CD5 antigen might not be detectable by immunohistochemistry (Tables 3 and 6).…”
Section: Discussionmentioning
confidence: 77%
“…Kuratsune et al [4] reported the first case of DLBCL that non-cohesively proliferated into the splenic red pulp and demonstrated clinicopathological features of malignant histiocytosis. Since their initial report, only 18 cases of DLBCLs non-cohesively infiltrating the splenic red pulp have been reported [4][5][6][7][8][9][10][11][12][13]. These reports support the existence of DLBCL manifesting in the splenic red pulp (DLBCLRP).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Necrosis is present in some cases and hilar lymph nodes are often involved. Distinction from low-grade splenic B-cell lymphomas with predominantly red pulp involvement is usually straightforward, given the large cell size and other highgrade morphological features, such as brisk mitotic activity, apoptosis and single cell necrosis, as well as an elevated Ki-67 proliferation index, which is usually >75 % [54,55].…”
Section: Other Splenic Lymphomas With Predominantly Red Pulp Diseasementioning
confidence: 99%